Sekolah Adiwiyata sebagai Pengembangan Masyarakat Desa Kedewan dalam Meningkatkan Potensi Wilayah - Riska Novitasari; Yuniati Fadilah; Sri Rahaju (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Environmental education is one of the initiatives to provide the school students with environmental awareness. Adiwiyata is a program which aims to create an environmentally friendly and cultured school. This program is conducted on the basis of three main principles, namely education, participation and sustainability. All school residents are expected to have the character and culture of the environment in daily activities, both at school and at home. To reach Adiwiyata School, every school must manage environmentally friendly supporting facilities. Greening the school environment is one form of adiwiyata activities in Kedewan Village. This activity was conducted at two locations namely SDN Kedewan 1 and SMPN 1 Kedewan. The purpose of this activity is to establish a fertile and beautiful family medicinal plant garden and to increase awareness of the school community regarding the benefits of family medicinal plants, as well as a form of development towards the Adiwiyata school. The tasks carried out in the form of seed and seedling planting are carried out together by the school community. Keywords: Environmental education, Planting activity, School community